The impact of holding major sports competitions on the brand of the state (on the example of the olympic games in sochi and the world football cup in Russia) - Markushina, N. Yu.; Parthenonok, N. L.; Askerova, E. F.; Bakhshiev, D. Z. (Theory and Practice of Physical Culture, 2022)
bstractObjective of the study was to determine the impact of major sports competitions on the brand of the state on the ex-ample of the Olympic Games in Sochi and the World Cup in Russia.Methods and structure of the study. When writing the article, a comparative analysis of the ratings of state brands, reports of the tourism and investment markets was used, and a case study was conducted based on reports on two major sports competitions in Russia.Results and conclusions. Noting the improvement in the positions of the Russian Federation in the ranking of national brands after major competitions, the article highlights the following factors for promoting the brand of the state: the visit of the first persons of the states during the competitions and the holding of high-level meetings taking into account the con-tinued sanctions regime and very limited visits by most European leaders to Russia), attracting extrabudgetary investments and economic growth, developing a number of infrastructure elements, adapting the tourism sector in accordance with modern international requirements and standards, as well as a significantly increasing tourist flow, and therefore familiarity with national history, culture and traditions. These criteria are universal for analyzing the successful impact of major sports competitions and can be used to analyze the evolution of the brand of any state.